Acoustic printing of conductive polymers - Ethan Trepka; Lauren Cooper; Kenneth Brinson; Samuel Thompson; Marigold Gil Malinao; Nicholas J. Rommelfanger; Polly Fordyce; Guosong Hong (Proceedings of the National Academy of Sciences, 2025)
Fabricating materials within optically opaque structures, such as biological tissue, is a considerable challenge. Recently, ultrasound-based printing (“sonoprinting”) approaches have emerged as a promising strategy to address this challenge. However, an approach to sonoprint conductive materials has yet to be realized, limiting potential bioelectronic applications. Here, we extend sonoprinting to conductive materials by designing temperature-based and pressure-based methods to polymerize conductive polymers with focused ultrasound (FUS). Our temperature-based approach relies on the acoustic attenuation of the surrounding medium to generate heat under FUS, whereas our pressure-based approach leverages the acoustic vaporization of perfluorohexane double emulsions to trigger polymerization. We demonstrate that both approaches can be used to print the conductive polymer poly(3,4-ethylenedioxythiophene) (PEDOT) through optically opaque hydrogels and biological tissue with high spatial resolution. Taken together, our results establish complementary temperature- and pressure-based methods for sonoprinting conductive polymers, paving the way for future efforts to fabricate bioelectronic interfaces in tissue.